To compare the functional and radiological outcome between external fixation and volar plating for the treatment of intraarticular distal end radius fractures - Atul Kumar Saroj; Ashutosh Verma; Mohd. Baqar Abbas; Upendra Kumar Patel; Virendra Kumar (Asian Journal of Medical Sciences, 2023)
Background: Fracture of distal radius may be stable that is extra-articular, non-comminuted without distal radio ulnar joint disruption or unstable that is intra-articular, comminuted displaced with distal radio ulnar joint disruption. Complications of unstable fractures are shortening due to bone loss or due to resorption of the cancellous bone from metaphysis, resistant deformity, residual pain, late collapse, radio carpal arthritis and gross functional impairment. Aims and Objective: The purpose of this study to compare the relative efficacy of external fixation versus plating with regard to functional and radiological outcome. Materials and Methods: Total of 60 patients having intraarticular distal end radius fracture were included in this study and was equally divided into two groups, one group treated by external fixator other group with volar locking compression plate with or without augmentation by k-wire. Follow-up was done after 2 weeks, 4 weeks, 6 weeks and 3 ,6 and 12 months. The radiological evaluation was performed with Sarmiento’s Modification of Lindstrom’s Criteria. With the Modified Mayo Wrist Score, the patient’s functional outcomes were assessed and both groups were compared. Results: In this study we found that volar plate group had good to excellent outcome in 73% cases and 07% with fair outcome however with external fixator group found good to excellent in 50% cases and poor in 17% cases. Conclusion: In our study, we showed that the use of an external fixator and a volar locking plate for the treatment of intraarticular distal radial fractures were reliable. The relative simplicity of use, low surgical exposure, and decreased surgical trauma are benefits of external fixation. Despite these volar locking plates augmented with or without k wire had a good to excellent results in terms of early rehabilitation and less complications related to wrist joint. External fixator with ligamentotaxis provide significant good results in communited intraarticular distal end radius fracture.